CLINICAL CASE OF MULTIPLE HEART TUMORS IN NEWBORN - Гольцман, Елена Викторовна; Полонская, Ольга Викторовна; Кучма, Ольга Владиславовна; Маисеенко, Дмитрий Александрович; Галактионова, Марина Юрьевна (Mother and Baby in Kuzbass, 2019)
Heart tumors are a rare pathology, especially in children. They have a varied characteristic. This disease can affect any part of the organ, the pericardium, the myocardium, the valves, the internal tissue of the heart, as well as the septum between the ventricles or the atria. This article presents a clinical case of a newborn with multiple fatal heart tumors diagnosed at home.